Antiviral properties of Orthosiphon stamineus aqueous extract in herpes simplex virus type 1 infected cells - Nur Suhana Mohamad Ripim,; Nuraini Fazil,; Saidatul Nadrah Kholid Ibrahim,; Adibah Ahamad Bahtiar,; Yip, Chee Wai; Nazlina Ibrahim,; Norefrina Shafinaz Md Nor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A study was conducted to investigate the antiviral activity of aqueous extracts from Orthosiphon stamineus (OS). Extraction was done using different parts of OS. The whole plant except root (WPOS), leaves (LOS) and flowers (FOS) of OS were extracted using aqueous extraction method. Cytotoxicity was assessed using 3-(4,5-dimethylthiazol-2,5-diphenyl tetrazolium bromide (MTT) assay. Plaque reduction assays were carried out to evaluate the antiviral activity of OS extract against herpes simplex virus type 1 (HSV-1). These include post-treatment, pre-treatment and virucidal assays. High antiviral activity was observed in post-treatment and virucidal assay with 100% reduction of HSV-1 plaque at 0.39 mg/mL in LOS, FOS and WPOS. In pre-treatment assay, 79%, 84% and 97% plaque reduction using the same concentration was observed in FOS, LOS and WPOS, respectively. In conclusion, this study showed that OS aqueous extract has promising potential to be explored as anti-HSV-1 agent regardless of the mode of treatment.